The tale of Jemima Puddle-Duck : a story about trust - Jennings, Karen; Pierce, Mark; Carter, Maureen (New York : Reader's Digest Young Families, 2006)
Wanting to hatch her own eggs, Jemima leaves the farm and trusts a sly fox to provide a nest. Includes parents' guide with discussion questions and activities to help children understand when it is safe to trust others.
Primary
Keywords: Jemima Puddle-Duck (Fictitious character) -- Juvenile fiction; Ducks -- Juvenile fiction; Fox -- Juvenile fiction; Trust -- Juvenile fiction; Eggs -- Incubation -- Juvenile fiction